2001
DOI: 10.1136/thorax.56.10.796
|View full text |Cite
|
Sign up to set email alerts
|

Lung function tests and risk factors for pneumonia in adults with chickenpox

Abstract: Background-Varicella is 25 times more likely to be complicated by pneumonia in adults than in children. Data on changes in lung function following pneumonia are limited. This study was undertaken to describe the epidemiological factors associated with pneumonia and to investigate lung function up to 1 year following chickenpox. Methods-Thirty eight consecutive suitable patients admitted to a university hospital were enrolled in the study; 19 had pneumonia and 19 did not. Epidemiological data and density of ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 21 publications
1
38
0
4
Order By: Relevance
“…The incidence of pneumonia in adults has been reported in two studies and varied between 0.32-1.36 cases per 100,000 person years [5,15]. Adults who develop chickenpox are at much greater risk of developing changes on their chest radiograph, with an incidence of 5-50% [3,[15][16][17][18][19]. A report of 110 chest radiographs from 114 USA army recruits who developed Varicella during basic training showed that 18 (16.3%) had interstitial and/or nodular infiltrates indicative of pneumonia [19].…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of pneumonia in adults has been reported in two studies and varied between 0.32-1.36 cases per 100,000 person years [5,15]. Adults who develop chickenpox are at much greater risk of developing changes on their chest radiograph, with an incidence of 5-50% [3,[15][16][17][18][19]. A report of 110 chest radiographs from 114 USA army recruits who developed Varicella during basic training showed that 18 (16.3%) had interstitial and/or nodular infiltrates indicative of pneumonia [19].…”
Section: Incidencementioning
confidence: 99%
“…However, chest symptoms may start before the appearance of the skin rash [16,24,25]. Physical findings are often minimal and chest radiographs typically reveal nodular or interstitial pneumonitis [16,19], as shown in figure 1.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pneumonia is the major and most frequent complication of varicella in healthy adults, with incidences being reported as high as 50% (1,2) and carries an overall mortality rate of between 10 and 30% (3). It has been reported that the susceptibility of varicella pneumonia in healthy adults is 25-fold greater than in children (4).…”
mentioning
confidence: 99%
“…In a limited number of cases, pulmonary symptoms may be present before the appearance of the skin rash (2). Patients demonstrate impaired gas exchange with progressive hypoxemia.…”
mentioning
confidence: 99%